ANALISIS PENGARUH MEKANISME KORDINASI TERHADAP SCHEDULE INSTABILITY DAN TOTAL BIAYA PADA LEVEL MPS DI ENTITAS RANTAI PASOK SEDERHANA DENGAN MEMPERTIMBANGKAN LEAD TIME - Elsa Rosyidah; Mochammad Aldy Anwar (2477 - 6165, 2019)
Instability in production planning (or better known as schedule instability) is unavoidable. This makes the company companies make various efforts to minimize the level of instability. There are several strategies that are generally used to minimize instability schedules, including freezing, safety stock / buffer. In this study, we will try to use a coordination approach to minimize the consequences of instability schedules in a simple supply chain. The simple supply chain system is the focus of this study consisting of one entrepreneur and one supplier integrated through a coordination mechanism (sharing information relating to order orders). This research will be conducted to study a full factorial experiment (full factorial experiment). A variety of different operational conditions are also considered such as: the uncertainty of financing, the cost structure, and the inventory policy applied by the company to be the part observed in this study. The results of this study, namely through the existence of a coordination mechanism, can reduce the level of schedule instability in each entity both manufacturing and supplier. In addition, through coordination it is also able to eliminate the transfer of risks that manufacturers often make to suppliers in the production planning section, as well as being able to reduce total costs to manufacturing or supplier entities. Through this research, it is expected to provide an understanding in the manufacturing industry of the importance of coordination in the supply chain system.